PERAN ZAKAT PRODUKTIF DALAM KESEJAHTERAAN EKONOMI MASYARAKAT: KOMPARASI BADAN AMIL ZAKAT MILIK NEGARA DAN SWASTA - Febriyanto, Satrio Alif (Journal of Islamic Law Studies, 2021)
Zakat is one of the main obligatory worship services that is carried out by giving some of the assets owned by a person to those entitled to receive it with the aim of realizing social justice in the community. With its form of giving, zakat is often considered to only be able to provide momentary benefits that tend to be consumptive. However, zakat can also be in the form of gifts that can provide long-term benefits that tend to be productive. The comparative study between state-owned and private institutions on the management of productive zakat is intended to find out the similarities and differences in the mechanism and governance of the distribution of money from muzakki to mustahik and how the utilization of zakat funds by mustahik with the final result in the form of solutions that can be applied by all amil zakat in Indonesia in increasing the utilization of productive zakat to improve the welfare of the people in their area. The research method used is juridical-normative through literature study and legislation related to zakat. Based on the results of the research that has been done, the management of productive zakat in Indonesia needs to be improved again, especially when carrying out the controlling function or supervision of zakat that has been given to mustahiq.